Dynamic Macroeconomics: A Didactic Numeric Model (2018)
Teaching Dynamic Macroeconomics at undergraduate courses relies exclusively on intuitive prose and graphics depicting behaviours and steady states of the main markets of the economy. But when the case of forward-looking agents and the macroeconomic implications of their actions are discussed, intuitions and graphical representations offered to students may lead to unsupported conclusions. This happens even if the teacher and students use the chapter upon a dynamic macroeconomic model of one of the most didactic and ordered texts ever published: Williamson (2014). In this paper we try to sustain this assertion.